2006
DOI: 10.1534/genetics.105.053686
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Genetic Incompatibility Causes Hybrid Male Sterility in Mimulus

Abstract: Much evidence has shown that postzygotic reproductive isolation (hybrid inviability or sterility) evolves by the accumulation of interlocus incompatibilities between diverging populations. Although in theory only a single pair of incompatible loci is needed to isolate species, empirical work in Drosophila has revealed that hybrid fertility problems often are highly polygenic and complex. In this article we investigate the genetic basis of hybrid sterility between two closely related species of monkeyflower, Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
178
7
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(199 citation statements)
references
References 89 publications
(72 reference statements)
13
178
7
1
Order By: Relevance
“…First, genetic mapping studies and laborious testcross analysis of the two major loci, hms1 and hms2, underlying hybrid sterility in the Oregon IM Â SF cross revealed that, while the M. nasutus hms2 incompatibility allele appears fixed within that species, the M. guttatus hms1 incompatibility allele is geographically localized at intermediate frequencies only in the IM population (Sweigart et al 2007). At least some of the individuals that we sampled from that population probably lacked that allele, since we did not observe complete sterility in any F 2 s in the cross with the M. nasutus SF population (Sweigart et al 2006). This strongly suggests that other loci are also involved in the sterility in this cross.…”
Section: Discussionmentioning
confidence: 74%
“…First, genetic mapping studies and laborious testcross analysis of the two major loci, hms1 and hms2, underlying hybrid sterility in the Oregon IM Â SF cross revealed that, while the M. nasutus hms2 incompatibility allele appears fixed within that species, the M. guttatus hms1 incompatibility allele is geographically localized at intermediate frequencies only in the IM population (Sweigart et al 2007). At least some of the individuals that we sampled from that population probably lacked that allele, since we did not observe complete sterility in any F 2 s in the cross with the M. nasutus SF population (Sweigart et al 2006). This strongly suggests that other loci are also involved in the sterility in this cross.…”
Section: Discussionmentioning
confidence: 74%
“…This contrasts with recent studies in Drosophila, where several genes have recently been cloned that cause almost complete reproductive isolation (Tinget al 1998;Barbash et al 2003;Presgraves 2003;Masly et al 2006). Likewise, major QTL for sterility are frequently detected in flowering plants (Moyle and Graham 2005;Fishman and Willis 2006;Sweigart et al 2006). The lack of major QTL for spore viability in ferns might be due to the use of DHLs for QTL mapping.…”
Section: Mechanisms Of Reproductive Isolationmentioning
confidence: 83%
“…Reproductive isolation has long been thought to accumulate gradually following population separation (Stebbins 1950;Dobzhansky 1951;Mayr 1963;Coyne and Orr 1989), but an understanding of reproductive isolation at the genetic and molecular levels did not emerge until recently. Genetic mapping of hybrid incompatibilities has provided insights into the number, location, and effect of the genetic factors underlying intrinsic postzygotic reproductive barriers (Naveira 1992;True et al 1996;Coyne et al 1998;Presgraves 2003;Tao et al 2003a,b;Moyle and Graham 2005;Fishman and Willis 2006;Sweigart et al 2006). Likewise, studying transmission ratio distortion (TRD) of marker loci in segregating hybrid populations has proven to be a sensitive assay for loci underlying reproductive barriers between parental populations (e.g., Fishman et al 2001a;Harushima et al 2002;Hall and Willis 2005).…”
mentioning
confidence: 99%
“…This is particularly striking in the context of other forms of male sterility in Mimulus hybrids. A nuclear Dobzhansky-Muller incompatibility causes complete pollen sterility (many unfilled pollen grains) in a fraction of F 2 hybrids between the same parental lines (Fishman and Willis, 2001;Sweigart et al, 2006). However, in this case, maximum seed set was also greatly reduced in male steriles (Sweigart et al, 2006), causing positive correlations between male and female fertility (Fishman and Willis, 2001).…”
Section: Discussionmentioning
confidence: 99%